Determinants of psychological resistance and recovery among women exposed to assaultive trauma. Issue 4 (28th February 2015) - Rusch, Heather L.; Shvil, Erel; Szanton, Sarah L.; Neria, Yuval; Gill, Jessica M.
Abstract Introduction Women exposed to potentially traumatic events (PTEs) are at high risk for developing psychiatric disorders, including posttraumatic stress disorder (PTSD), general anxiety disorder (GAD), major depressive disorder (MDD), and substance‐related disorders. However, this risk is not universal. Most women are resistant (i.e., remain asymptomatic), or recover following a brief symptomatic period. This study examined the psychological factors associated with resistant and recovered outcomes in a sample of high‐risk women exposed to assault‐related PTEs. Method One hundred and fifty‐nine women completed the Life Events Checklist and were administered the Structured Clinical Interview for DSM‐IV Axis I Disorders. This resulted in three groups: (1) no diagnosis (no past or current psychiatric disorder diagnosis; n = 56), (2) past diagnosis (a past psychiatric disorder diagnosis, but none currently; n = 31), and (3) current diagnosis (a current diagnosis of one or more psychiatric disorders; n = 72). Groups were compared on sociodemographics, PTE exposure, psychopathology, health‐related quality of life (HRQOL), and psychological resilience‐related factors. Results The majority of respondents (79%) did not develop chronic PTSD following assault exposure, and the most common psychiatric outcome was MDD (30%). High endorsement of mastery and social support were associated with the no diagnosis group; and greater reports of mastery and posttraumatic growth were associated with recovery from a past psychiatric disorder. Furthermore, both resilient groups (i.e., no diagnosis and past diagnosis) scored higher on HRQOL measures compared with the current diagnosis group (P < 0.001). Conclusion Psychological resilience has ramifications to health and well‐being, and identifying these factors has potential to inform preventive strategies and treatment interventions for assault exposed women.